Status and Development Trend of Aquaculture and Fisheries in Nepal - Gautam, Sarita; Sapkota, Prashanta (Nepalese Journal of Aquaculture and Fisheries, 2023)
Nepal’s fisheries sector, deeply rooted in historical practices, constitutes crucial component of the nation’s natural wealth, buoyed by its diverse geographical features and ample water resources. While traditional capture fisheries have historically played a significant role in fish production and employment, maintaining production levels presents challenges necessitating thorough reassessment. The landlocked geography compels a focus on inland finfish farming in the aquaculture subsector, supported by governmental initiatives such as the Fish Mission and Prime Minister Agriculture Modernization Project. The Terai belt, with its favorable climate, serves as a pivotal area for fish production, covering 89% of the total pond area. Nepal’s total fish production stands at 113,736 mt, with capture fisheries contributing 18% and aquaculture 82%, collectively employing around 0.52 million individuals. Fish consumption in Nepal is on the rise, with per capita availability increasing from 330 g to 3.92 kg between 1981/82 and 2022/23. Efforts from both the government and private sector aim to commercialize the sector, addressing issues of food security, poverty reduction, and creation of income and employment opportunities. Despite challenges, targeted endeavors through governmental initiatives, private sector involvement, and sustainable practices are vital to unlocking the full economic, employment, and food security potential of fisheries sector.